Potential Anemia as a Risk Factor for Angular Cheilitis and Pseudomembranous Candidiasis: Case Report - Megawati, Ani (Jurnal Kesehatan Gigi, 2024)
Angular cheilitis and pseudomembranous candidiasis are oral infections caused by Candida albicans. Angular cheilitis patients also experience oral candidiasis because the Candida reservoir is intraoral. Iron deficiency anemia was closely related to this infection. A 50-year-old female patient complaint of pain in the commissure and tongue 3 weeks ago. Extraoral examination showed anemic conjunctiva and fissure erythema with crusting in bilateral commissures. Intraoral examination showed atrophy of papillae with a yellowish-white plaque that can be scraped off and leaves erythema on the tongue. A complete blood examination was performed and showed a decrease in hemoglobin, hematocrit, erythrocytes, MCV, MCH, and MCHC. The patient was diagnosed angular cheilitis and pseudomembranous candidiasis with iron deficiency anemia. The therapy was miconazole 2% cream, nystatin oral suspension 100.000 IU/ml, and iron supplements. The lesions healed after 2 weeks of therapy and the patient was consulted to an internist. The patient has Angular cheilitis and pseudomembranous candidiasis triggered by iron deficiency anemia. Iron deficiency anemia causes a decrease in salivary transferrin protein which is fungistatic so that Candida grows excessively. Angular Cheilitis therapy is miconazole cream which inhibit the synthesis of ergosterol and nystatin for candidiasis therapy which works by binding to Candida plasma membrane sterols, causing leakage and then death. Iron deficiency anemia therapy is iron supplements; however, drug therapy alone is less effective, and consultation with an internist is required for further therapy. Anemia has big potential to be a risk factor for angular cheilitis and pseudomembranous candidiasis so comprehensive treatment is needed.